Redesigning a Science Teacher Preparation Program for Equity: Using Critical Whiteness Pedagogy to Educate Secondary Science Preservice Teachers - McCausland, Jonathan; McDonald, Scott (Innovations in Science Teacher Education, 2023)
In this article, we describe the redesign of a secondary science teacher preparation program. The goal of the redesign was to help preservice teachers in the program become more justice-oriented science teachers. We describe the impetus for the redesign and how we went about redesigning the program through an iterative process of conjecture mapping (Sandoval, 2014), and we highlight important elements of the program. Ultimately, we argue that teacher preparation programs can draw upon practice-based teacher education and critical whiteness pedagogy to assist preservice teachers in becoming justice-oriented science teachers. By blending practice-based teacher education and critical whiteness pedagogy, preservice science teachers can practice being justice oriented, helping them become novice critical whiteness ambitious science teachers.